Expressions parenthétiques dans un corpus parallèle français-grec : les adverbiaux de conviction personnelle - Fryni Kakoyianni-Doa (Discours)
This paper aims at describing and comparing a subset of utterance-level French and Greek adverbials that express the personal conviction of the speaker towards the information transmitted. In particular, adverbial forms of personal opinion which have close relation with the parenthetical verbs to think, to suppose are examined in a new French-Greek parallel corpus.